Improving the socialization of new hires using gamification in remote working environments - Goh, Lynette Ying Qin (Nanyang Technological University, 2021)
Many organizations had to rapidly adapt to a remote working environment because of the COVID-19 global pandemic social distancing restrictions enforced and employees reported feelings of isolation. The organizational socialization process of new hires was impacted as organizations’ onboarding tactics were disrupted, where either some institutionalized tactics could not be shifted online or the challenges of a remote working environment just emphasized the gaps more in an organization whose tactics are predominantly individualized. This dissertation aimed to extend knowledge of practical methods people use in remote working environments for socialization and explore how gamification can be used to effectively socialize new hires by encouraging them to be more proactive in such environments. Following a user-centred design methodology, the Octalysis gamification design framework was used together with requirements gathered from qualitative interviews conducted with new hires onboarded during enforced strict social distancing restrictions, hiring managers and Human Resource (HR) professionals to design a gamification solution called ‘OnboardingMojo’. This solution was then evaluated with a usability test and participants found the solution fun. They appreciated the features provided that helped them get to know their colleagues as that supports their self-efficacy, though the quality of personal interactions would be the key factor for organizational commitment than the solution itself. These results suggested that there was potential for gamification to be used as a complementary solution to help new hires be proactive in their organizational socialization process even in a remote working environment.